Visages "mangés" par les détails. Réflexions autour d’une double rhétorique de la ressemblance aux débuts de la photographie - Maddalena Parise (Images Re-Vues, 2006)
The particularly ambiguous position of the detail in relation to first photographic portraits is explored in the context of the construction of the idea of resemblance in photography’s very earliest days. Through contemporary writing and by analysing the images the aim is to define the complex role of the detail in establishing a double rhetoric of photographic resemblance intended, from its beginnings, to be as much constructed (by the means of representation) as exact (by effect of reference). Depending on its quality, its position, and how it is received, the detail is the mark of this ambiguity, as it presents itself both as the illusion of perfect imitation and as a recalcitrant presence of the subject. This analysis is deliberately limited to the daguerreotype in so far as this object, often reduced to the status of emblem of photographic exactitude, still condenses the contradictions of an image constructed according to the means of representation while at the same time producing the troubling effect of a presence.